2011
DOI: 10.51815/fjsr.110704
|View full text |Cite
|
Sign up to set email alerts
|

Is there something peculiar about Finnish views on alcohol addiction? – A cross-cultural comparison between four northern populations

Abstract: Empirical studies have continued to display that Finns get heavily intoxicated more often than other Nordic people. This study asks whether Finnish views on alcohol problems and alcohol addiction differ from those of some other northern populations. This issue is studied by comparing survey results from Finland, Canada, Sweden and St. Petersburg, Russia. The data comprised 3 703 adults and it was analysed with standard descriptive methods and logistic regression analysis. Finnish general population respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, not only the terminology used but also images of the suggested causes and character of drinking and drug use have been found to be both manifold and variable. For example, a number of studies have shown that the dominant perceptions of the severity of addiction-related problems (for the individual and for society), the assumed nature of addiction, and the way options for recovery from addiction are rated all vary considerably across different substances linked to addiction, and also across different populations and countries (e.g., Blomqvist, 2009 , 2012 ; Blomqvist et al, 2014 ; Hirschovits-Gerz et al, 2011 ; Holma et al., 2011 ). Several studies have also demonstrated that variations in how phenomena such as “dependence” or “addiction” are constituted actually develop in response to concrete practical needs that arise within specific contexts (cf.…”
mentioning
confidence: 99%
“…Furthermore, not only the terminology used but also images of the suggested causes and character of drinking and drug use have been found to be both manifold and variable. For example, a number of studies have shown that the dominant perceptions of the severity of addiction-related problems (for the individual and for society), the assumed nature of addiction, and the way options for recovery from addiction are rated all vary considerably across different substances linked to addiction, and also across different populations and countries (e.g., Blomqvist, 2009 , 2012 ; Blomqvist et al, 2014 ; Hirschovits-Gerz et al, 2011 ; Holma et al., 2011 ). Several studies have also demonstrated that variations in how phenomena such as “dependence” or “addiction” are constituted actually develop in response to concrete practical needs that arise within specific contexts (cf.…”
mentioning
confidence: 99%